A review of Vehicle Routing Problem with Selective Pickup Point and Delivery - Qi, Shi (International Journal of Computer Science and Information Technology, 2024)
The problem of picking up and delivery vehicle routing is that one delivery point can correspond to multiple pickup points, and one of these pickup points needs to be selected for pickup before delivery. With the reform of the retail industry, the omnichannel retail model has gradually become popular, which provides consumers with a variety of choice of pick-up points in collaboration with online e-commerce and offline stores. This paper gives a systematic overview of the relevant operational research model and its solution for the pick-up and delivery vehicle routing problem considering the selection of pick-up points, hoping to encourage logistics community and transportation science to do more research in this emerging field.